Convolution and limit theorems for conditionally free random variables - Bożejko, Marek; Leinert, Michael; Speicher, Roland (Pacific journal of mathematics, 1996)
We introduce the notion of a conditionally free product and conditionally free convolution. We describe this convolution both from a combinatorial point of view, by showing its connection with the lattice of non-crossing partitions, and from an analytic point of view, by presenting the basic formula for its R-transform. We calculate explicitly the distributions of the conditionally free Gaussian and conditionally free Poisson distribution.